Advanced glycated end-products (AGE) during haemodialysis treatment: discrepant results with different methodologies reflecting the heterogeneity of AGE compounds - Henle, Thomas; Deppisch, Reinhold; Beck, Werner; Hergesell, Olaf; Hänsch, Gertrud Maria; Ritz, Eberhard (Nephrology, dialysis, transplantation, 1999)
There has been much recent interest in accumulation of advanced glycation end-products (AGE) in uraemic patients. Analysis of AGE has been difficult, because commonly used methodologies, i.e. immunodetection assays or fluorescence measurements, reflect group reactivity and are not specific for chemically defined substances. Some investigators measured individual AGE compounds, e.g. pentosidine, carboxymethyllysine, pyrraline or imidazolone, but a systematic assessment of known compounds using specific HPLC methods in diabetic and non-diabetic end-stage renal disease (ESRD) patients during treatment has not been performed.
Gesehen am 11.11.2021